Crustal deformations associated with the great Sumatra-Andaman earthquake deduced from continuous GPS observation - Hashimoto, M; Choosakul, N; Hashizume, M; Takemoto, S; Takiguchi, H; Fukuda, Y; Frjimori, K (TerraPub, 2006)
We analyzed continuous GPS data from more than 20 sites in Asia, Australia and islands in Indian Ocean in order to detect crustal deformations associated with the Sumatra-Andaman earthquake of December 26, 2004. Coseismic steps can be recognized at sites about 3,000 km away from the epicenter such as Kunming in south China, Quezon in Philippines, and Diego Garcia Island in central Indian Ocean. The largest displacement of about 26 cm is found at Phuket in Thailand about 600 km away from the epicenter, about twice as large as that at Sampari, the nearest site in northern Sumatra. These observations suggest that as large slip as 14 m occurred beneath the Nicobar Islands. Large postseismic displacements are observed at Phuket and Sampari after the mainshock, but the former is three times larger than the latter. This suggests that the spatial distribution of afterslip is different from the coseismic slip distribution. The temporal variation of postseismic displacements can be explained by a logarithmic function derived from rate-state dependent friction law with short characteristic time. The area where coseismic displacements from the Nias earthquake of March 28, 2005 are detected is much smaller than that from the December mainshock, but displacement at Sampari is larger than that during the mainshock. These displacements suggest less than 4 m slip on a shallow dipping thrust fault and resultant moment release is smaller than that estimated from seismological data. Finally, total moment released by afterslip amounts to 3.83 × 10 22 Nm which is equivalent to Mw 8.99 for about ﬁve months, including the afterslip for the Nias earthquake.
Keywords: Sumatra-Andaman earthquake; Nias earthquake; Coseismic deformation; Postseismic deformation; GPS; Fault model; 26 December 2004; SLIP